Extra-thick steel material for flanges with excellent strength and low-temperature impact toughness and its manufacturing method
A steel composition and controlled forging process for wind power generator flanges address the challenge of residual voids and impurities, achieving high strength and toughness in thick materials by optimizing alloy elements and forging steps, enhancing the material's internal soundness and low-temperature impact toughness.
Patent Information
- Application Number
- JP2024536531
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-21
- Filing Date
- 2022-12-19
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2042-12-19
AI Technical Summary
Existing methods for manufacturing thick steel materials for wind power generator flanges face challenges in compressing residual voids at the center, leading to crack initiation points and deteriorated material quality due to impurities and segregation, especially in materials exceeding 200 mm thickness, which can result in lamellar tearing and reduced low-temperature impact toughness.
A steel composition with specific alloy elements (C, Si, Mn, Al, P, S, Nb, V, Ti, Cr, Mo, Cu, Ni, Ca) and controlled forging processes (primary upset, bloom forging, secondary upset, round forging, tertiary upset, and ring forging) to achieve a microstructure with fine NbC precipitates and controlled porosity, ensuring a thickness of 200 to 500 mm with tensile strength of 500 to 700 MPa, yield strength of 350 MPa, and Charpy impact toughness of 50 J at -50°C.
The method effectively compresses voids in the center, improving internal soundness and low-temperature impact toughness, resulting in a high-quality steel material suitable for flanges with excellent strength and toughness characteristics.
Smart Images

Figure 2025501540000001 
Figure 2025501540000002 
Figure 2025501540000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an extra-thick steel material for flanges having excellent strength and low-temperature impact toughness and a manufacturing method thereof, and more particularly to an extra-thick steel material for flanges having excellent strength and low-temperature impact toughness that can be used for wind power towers and systems, etc., and a manufacturing method thereof. [Background technology]
[0002] Wind power generation has been attracting attention as an environmentally friendly means of producing electricity, and wind power generators include parts such as tower flanges, bearings, and main shafts. Among these, tower flanges are joint parts required for connecting towers, and usually 5 to 7 flanges are used for one tower. Wind power generators are required to have high durability because they are installed on the sea or in extreme regions. In particular, in response to the demand for large-capacity energy production and high efficiency, the scale of wind towers is also increasing, and accordingly, there is a continuous demand for high strength, high toughness, and thick steel materials to be used. As the thickness of the material increases, the total deformation amount decreases, and the particles of the microstructure become larger, and the material tends to deteriorate due to defects in the material such as inclusions and segregation. Therefore, in order to improve the external soundness of steel materials, the concentration of impurities such as non-metallic inclusions and segregations is reduced, and cracks and voids on the surface and inside the material are controlled to the utmost.
[0003] In particular, in the case of extremely thick materials with a thickness of more than 200 mmt, the amount of deformation at the center of the material is not large, so if unsolidified shrinkage holes that occur during continuous casting or casting are not sufficiently compressed in the forging process, they will remain in the form of residual voids in the center of the flange. When the structure is subjected to axial stress in thickness, these residual voids can become the starting point of cracks, eventually causing damage to the entire equipment in the form of lamellar tearing. Therefore, a process is required to sufficiently compress the central void so that no residual voids exist before piercing (hole forging) and ring forging (product forming), which have a small amount of deformation.
[0004] The related Patent Document 1 is a technology for applying a strong reduction in a rough rolling process of a thick plate. Specifically, it utilizes a technology for determining a limit reduction rate for each thickness at which plate bite occurs from a strong reduction rate for each pass set to be close to the design allowable value (load and torque) of the rolling mill, a technology for distributing the reduction rate by adjusting the index of the thickness ratio for each pass in order to secure the target thickness of the rough rolling mill, and a technology for correcting the reduction rate based on the limit reduction rate for each thickness so that plate bite does not occur, and provides a manufacturing method in which the average reduction rate in the final three passes of rough rolling is about 27.5% based on 80 mmt. However, in the case of the above rolling method, the average reduction rate of the entire product thickness is measured, and in the case of an extremely thick material with a maximum thickness of 200 mmt or more, it is technically difficult to realize a high deformation up to the center where residual voids exist.
[0005] Another method for manufacturing an extremely thick product is to utilize a forging machine, which has a higher effective deformation per pass than a rolling mill. In Patent Document 2, a slab containing, by mass%, C: 0.08-0.20%, Si: 0.40% or less, Mn: 0.5-5.0%, P: 0.010% or less, S: 0.0050% or less, Cr: 3.0% or less, Ni: 0.1-5.0%, Al: 0.010-0.080%, N: 0.0070% or less, and O: 0.0025% or less, which satisfy the relationships of Formulas 1 and 2, and the remainder being Fe and unavoidable impurities, is hot forged with a cumulative reduction of 25% or more. It explicitly states that a thick, high-toughness, high-strength material can be manufactured by heating the steel sheet to between the Ac3 point and 1,200°C, hot rolling it to a cumulative reduction of 40% or more, quenching it at a temperature of between the Ar3 point and 350°C or a low temperature below the Ar3 point, or by performing a tempering heat treatment process at a temperature of 450 to 700°C, and having a plate thickness of 100 mmt or more, a yield strength of 620 MPa or more, and an absorbed energy of 70 J or more when evaluated for low-temperature impact toughness at -40°C.
[0006] However, in the above manufacturing method, if the cumulative reduction is too large, surface defects may occur due to localized deformation concentration, and in particular, if surface or subsurface defects exist in the slab before forging, the defects may propagate during the forging process, causing further deterioration of the surface quality in the product after rolling. Also, if the forging reduction per pass is insufficient, it is difficult to sufficiently close the voids remaining in the center even if the cumulative reduction is large, and the rolling process is also not suitable for controlling the voids and structure in the center of an extremely thick material because the effective deformation of the center is smaller than that of the surface deformation.
[0007] On the other hand, Patent Document 3 discloses a method for producing a thick, high-strength steel plate of 100 mmt or more and having a yield strength of 620 MPa or more, through steps of heating a material provided with a predetermined alloy composition to 1200 to 1350°C, hot forging with a cumulative reduction of 25% or more, heating to a temperature between the Ac3 point and 1200°C and hot rolling with a cumulative reduction of 40% or more, reheating to a temperature between the Ac3 point and 1050°C, quenching at a temperature of the Ac3 point or more to a temperature of 350°C or less or the Ar3 point or less, whichever is lower, and tempering at a temperature of 450°C to 700°C.
[0008] However, in the case of the ultra-high strength steel plate, the carbon equivalent (Ceq) and hardenability index (DI) are high, making it vulnerable to surface cracks during casting, and in the case of flange steel materials manufactured by normalizing heat treatment, the process conditions cannot be easily applied. In addition, when the carbon equivalent (Ceq) and hardenability index (DI) are high, cracks are likely to occur on the surface of the cast slab due to the generation of surface hard structure during the secondary cooling process of steelmaking, and the cracks may propagate during the forging process, degrading the surface quality of the final product. Therefore, a forging method has been proposed to improve the internal soundness of the final product by crimping the void in the center, but no practical method has been presented to ensure both appropriate material properties and excellent surface quality of the flange steel. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Korean Patent Publication No. 10-2012-0075246 [Patent Document 2] Korean Patent Publication No. 10-2017-0095307 [Patent Document 3] Korean Patent Publication No. 10-2017-0095307 Summary of the Invention [Problem to be solved by the invention]
[0010] An object of the present invention is to provide an extra-thick steel material for flanges having excellent strength and low-temperature impact toughness, and a method for producing the same. The object of the present invention is not limited to the above-mentioned contents, and a person skilled in the art will have no difficulty in understanding further object of the present invention from the overall contents of this specification. [Means for solving the problem]
[0011] The extra-thick steel material for flanges of the present invention is In weight percent, it consists of C: 0.05-0.2%, Si: 0.05-0.5%, Mn: 1.0-2.0%, Al: 0.005-0.1%, P: 0.01% or less, S: 0.015% or less, Nb: 0.001-0.07%, V: 0.001-0.3%, Ti: 0.001-0.03%, Cr: 0.01-0.3%, Mo: 0.01-0.12%, Cu: 0.01-0.6%, Ni: 0.05-1.0%, Ca: 0.0005-0.004%, and the remainder being Fe and other unavoidable impurities, and Ceq according to the following relational formula 1 satisfies the range of 0.35-0.55, The average crystal grain size of ferrite present at the center of the steel material is 25 μm or less, and the steel material has a fine structure containing 5 to 30 area % of pearlite and the remainder of ferrite, The porosity of the steel core, which is the area from the surface of the steel to the thickness direction of 3 / 8t to 5 / 8t, is 0.05 mm 3 / g or less, and Deformation-induced NbC precipitates of 5 to 50 nm observed in the cross section of the steel material were 1 μm in diameter. 2 The number of coarse precipitates of 100 nm or more is 10 or more per grain, and the number of coarse precipitates of 100 nm or more is 5 or less per grain. [Relationship 1] Ceq=[C]+[Mn] / 6+([Cr]+[Mo]+[V]) / 5+([Ni]+[Cu]) / 15 In the above relational formula 1, [C], [Mn], [Cr], [Mo], [V], [Ni] and [Cu] respectively represent the contents (weight%) of C, Mn, Cr, Mo, V, Ni and Cu contained in the steel, and 0 is substituted when these elements are not intentionally added.
[0012] The steel material may have a thickness of 200 to 500 mm. The above steel material preferably has a tensile strength of 500 to 700 MPa, a yield strength of 350 MPa or more, and an absorbed energy value in a -50°C Charpy impact test of 50 J or more. The maximum surface crack depth of the above steel material is preferably 0.1 mm or less (including 0).
[0013] The method for producing an extra-thick steel material for flanges of the present invention comprises the steps of: a step of preparing a slab containing, by weight, C: 0.05-0.2%, Si: 0.05-0.5%, Mn: 1.0-2.0%, Al: 0.005-0.1%, P: 0.01% or less, S: 0.015% or less, Nb: 0.001-0.07%, V: 0.001-0.3%, Ti: 0.001-0.03%, Cr: 0.01-0.3%, Mo: 0.01-0.12%, Cu: 0.01-0.6%, Ni: 0.05-1.0%, Ca: 0.0005-0.004%, and the remainder being Fe and other inevitable impurities, and having a Ceq of 0.35-0.55 according to the following relational formula 1, heating the slab to a temperature range of 1100-1300°C; The heated slab is first upset at a forging ratio of 1.3 to 2.4, and then bloom forged at a forging ratio of 1.5 to 2.0; Reheating the bloom forged material to a temperature range of 1100 to 1300 ° C.; The reheated bloom material is secondarily upset at a forging ratio of 1.3 to 2.3, and then round forged at a forging ratio of 1.65 to 2.25; The round forged material is subjected to a third upsetting at a temperature below the recrystallization temperature defined by the following Relation 2, with a forging ratio of 2.0 to 2.8 so that the cumulative reduction is 10% or more; After the tertiary upset material is drilled, it is reheated to a temperature range of 1100 to 1300 ° C., and then ring forged with a forging ratio of 1.0 to 1.6; The method is characterized by including a step of performing a normalizing heat treatment in which the ring-forged material is heated to a temperature range of 820 to 930°C based on the temperature measurement standard at the center thereof, held for 5 to 600 minutes, and then air-cooled to room temperature. [Relationship 1] Ceq=[C]+[Mn] / 6+([Cr]+[Mo]+[V]) / 5+([Ni]+[Cu]) / 15 In the above relational formula 1, [C], [Mn], [Cr], [Mo], [V], [Ni] and [Cu] respectively represent the contents (weight%) of C, Mn, Cr, Mo, V, Ni and Cu contained in the steel, and 0 is substituted when these elements are not intentionally added. [Equation 2] T nr (℃)=887+464×[C]+890×[Ti]+363×[Al]-357×[Si]+(6445×[Nb]-644×[Nb] 1 / 2 )+(732×[V]-230×[V] 1 / 2 ) In the above Relational Formula 2, [C], [Ti], [Al], [Si], [Nb], and [V] respectively represent the contents (weight%) of C, Ti, Al, Si, Nb, and V contained in the steel material, and 0 is substituted when these components are not intentionally added.
[0014] The slab may be manufactured using one of a continuous casting process, a semi-continuous casting process, and an ingot casting process. If the size of the forging surface punched out during the first upsetting is initially 700 mm x 1800 mm, it can be (1000~1200 mm) x (1800~2000 mm). In the case of the above bloom forging, if the size of the forged surface at the time of completion of forging is initially (1000-1200 mm) x (1800-2000 mm), it can be (1450-1850 mm) x (2100-2500 mm).
[0015] When the secondary upsetting and round forging are completed, the product size can be (1450~1850Φ) x (1300~1700mm). When the above tertiary upsetting is completed, the product size can be (2300~2800Φ) x (400~800mm). The maximum thickness of the flange made of the above steel material can be 200 to 500 mm, the inner diameter can be 4000 to 7000 mm, and the outer diameter can be 5000 to 8000 mm. Effect of the Invention
[0016] According to the present invention having the above-mentioned configuration, by optimizing the forging process, the void in the center of the steel material can be crimped to improve the internal integrity of the final product, and an extremely thick steel material that can be used for flanges having excellent not only strength but also low-temperature impact toughness can be effectively provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention relates to an extra-thick steel material for flanges having excellent strength and low-temperature impact toughness and a manufacturing method of the product, and the preferred embodiments of the present invention will be described below. The embodiments of the present invention may be modified in various ways, and the scope of the present invention should not be construed as being limited to the embodiments described below. The embodiments are provided to explain the present invention in more detail to those skilled in the art to which the present invention pertains. The extra-thick steel material for flanges having excellent strength and low-temperature impact toughness according to the present invention will be described in more detail below.
[0018] The extra-thick steel material for flanges of the present invention, which is excellent in strength and low-temperature impact toughness, contains, by weight, C: 0.05-0.2%, Si: 0.05-0.5%, Mn: 1.0-2.0%, Al: 0.005-0.1%, P: 0.01% or less, S: 0.015% or less, Nb: 0.001-0.07%, V: 0.001-0.3%, Ti: 0.001-0.03%, Cr: 0.01-0.3%, Mo: 0.01-0.12%, Cu: 0.01-0.6%. The steel material is made up of 0.05-1.0% Ni, 0.0005-0.004% Ca, and the remainder is Fe and other inevitable impurities, and Ceq according to the relational formula 1 satisfies the range of 0.35-0.55. The average crystal grain size of ferrite present at the center of the steel material is 25 μm or less, and the steel material has a fine structure containing 5-30 area % pearlite and the remainder ferrite. The porosity of the center of the steel material, which is the region of 3 / 8t to 5 / 8t from the surface of the steel material in the thickness direction, is 0.05 mm 3 / g or less, and deformation-induced NbC precipitates of 5 to 50 nm observed in the cross section of the steel material are less than 1 μm 2The number of coarse precipitates of 100 nm or more is 10 or more per grain, and the number of coarse precipitates of 100 nm or more is 5 or less. The alloy composition of the present invention will be described in more detail below. Unless otherwise specified, % and ppm described in the alloy composition are based on weight.
[0019] ·Carbon (C): 0.05~0.20% Carbon (C) is the most important element for ensuring basic strength, so it must be contained in steel within an appropriate range. To obtain such an effect, 0.05% or more of carbon (C) can be added. Preferably, 0.10% or more of carbon (C) is added. On the other hand, if the carbon (C) content exceeds a certain level, the fraction of pearlite increases during normalizing heat treatment, which may excessively exceed the strength and hardness of the base material, and this may cause surface cracks during forging, resulting in a decrease in low-temperature impact toughness and lamellar tear resistance in the final product. Therefore, in the present invention, it is preferable to limit the carbon (C) content to 0.20%, and the more preferable upper limit of the carbon (C) content is 0.18%.
[0020] Silicon (Si): 0.05-0.50% Silicon (Si) is a substitutional element that improves the strength of steel by solid solution strengthening and has a strong deoxidizing effect, making it an essential element for the production of clean steel. Therefore, silicon (Si) should be added at 0.05% or more, and more preferably at 0.20% or more. On the other hand, if a large amount of silicon (Si) is added, it may generate a martensite-austenite (MA) phase, excessively increase the strength of the ferrite matrix, and cause deterioration of the surface quality of extremely thick products, so the upper limit of the silicon (Si) content is preferably limited to 0.50%. A more preferable upper limit of the silicon (Si) content is 0.40%.
[0021] Manganese (Mn): 1.0-2.0% Manganese (Mn) is a useful element that improves strength through solid solution strengthening and improves hardening ability so that a low-temperature transformation phase is generated. Therefore, in order to ensure a tensile strength of 550 MPa or more, it is preferable to add 1.0% or more of manganese (Mn). More preferably, the manganese (Mn) content is 1.1% or more. Meanwhile, manganese (Mn) forms MnS, which is an elongated nonmetallic inclusion, together with sulfur (S), thereby reducing toughness and acting as an impact initiation point, which is a factor in rapidly reducing the low-temperature impact toughness of the product. Therefore, the manganese (Mn) content should be controlled to 2.0% or less, and more preferably, the manganese (Mn) content is 1.5% or less.
[0022] Aluminum (Al): 0.005~0.1% Aluminum (Al), together with silicon (Si), is one of the powerful deoxidizing agents in the steelmaking process, and in order to obtain this effect, it is preferable to add 0.005% or more. A more preferable lower limit of the aluminum (Al) content is 0.01%. On the other hand, if the aluminum (Al) content is excessive, the proportion of Al2O3 in the oxidized inclusions generated as a result of deoxidation increases excessively, causing the size of the inclusions to become coarse, which makes it difficult to remove the inclusions during refining, and this can be a factor in reducing low-temperature impact toughness. Therefore, it is preferable to control the aluminum (Al) content to 0.1% or less. A more preferable aluminum (Al) content is 0.07% or less.
[0023] Phosphorus (P): 0.010% or less (including 0%) Sulfur (S): 0.0015% or less (including 0%) Phosphorus (P) and sulfur (S) are elements that induce brittleness at grain boundaries or form coarse inclusions, and therefore, in order to improve resistance to brittle crack propagation, it is preferable to limit phosphorus (P) to 0.010% or less and sulfur (S) to 0.0015% or less.
[0024] Niobium (Nb): 0.001-0.07% Niobium (Nb) is an element that precipitates in the form of NbC or NbCN to improve the strength of the base material. In addition, niobium (Nb) that is dissolved during high-temperature reheating precipitates very finely in the form of NbC during rolling, suppressing the recrystallization of austenite, and has the effect of refining the structure. Therefore, niobium (Nb) is preferably added at 0.001% or more, and the more preferred niobium (Nb) content is 0.005% or more. On the other hand, when niobium (Nb) is added in excess, undissolved niobium (Nb) is generated in the form of TiNb(C,N), which becomes a factor that inhibits low-temperature impact toughness, so the upper limit of the niobium (Nb) content is preferably limited to 0.07%. The more preferred niobium (Nb) content is 0.065% or less.
[0025] Vanadium (V): 0.001-0.3% Vanadium (V) almost completely redissolves during reheating, so the strengthening effect due to precipitation or dissolution during the rolling process is insufficient. However, in the case of extremely thick forged materials, the air cooling rate is very slow, so it precipitates as very fine carbonitrides during the cooling process or additional heat treatment process, which has the effect of improving strength. In order to fully obtain such an effect, it is necessary to add 0.001% or more of vanadium (V). A more preferable lower limit of the vanadium (V) content is 0.01%. On the other hand, if the content is excessive, the surface hardness of the slab increases excessively due to its high hardening ability, which not only acts as a cause of surface cracks during flange processing, but also causes a rapid increase in manufacturing costs, making it commercially unprofitable. Therefore, it is better to limit the vanadium (V) content to 0.3% or less. A more preferable vanadium (V) content is 0.25% or less.
[0026] Titanium (Ti): 0.001-0.03% Titanium (Ti) is a component that precipitates as TiN during reheating, inhibits the growth of prior austenite grains at high temperatures, and greatly improves low-temperature toughness. To obtain such an effect, it is preferable to add 0.001% or more of titanium (Ti). On the other hand, if titanium (Ti) is added excessively, there is a possibility that the low-temperature toughness will decrease due to clogging of the continuous casting nozzle and crystallization in the center. In addition, titanium (Ti) combines with nitrogen (N) to form coarse TiN precipitates in the center of the thickness, which reduces the elongation of the product, and therefore may reduce the uniform elongation during the forging process and cause surface cracks. Therefore, the titanium (Ti) content is preferably 0.03% or less. The preferred titanium (Ti) content is 0.025% or less, and more preferably 0.018% or less.
[0027] Chromium (Cr): 0.01-0.30% Chromium (Cr) is an element that increases the hardenability and forms a low-temperature transformation structure, thereby increasing the yield strength and tensile strength. It is also an element that has the effect of preventing a decrease in strength by retarding the spheroidization rate of cementite. For this effect, 0.01% or more of chromium (Cr) can be added. On the other hand, if the chromium (Cr) content is excessive, M 23 The size and fraction of Cr-rich coarse carbides such as C6 increases, reducing the impact toughness of the product, and the solid solubility of niobium (Nb) in the product and the fraction of fine precipitates such as NbC decrease, which may cause a problem of reduced strength of the product. Therefore, in the present invention, the upper limit of the chromium (Cr) content can be limited to 0.30%. The preferred upper limit of the chromium (Cr) content is 0.25%.
[0028] Molybdenum (Mo): 0.01-0.12% Molybdenum (Mo) is an element that increases grain boundary strength and has a large effect on solid solution strengthening in ferrite, and is an element that effectively contributes to increasing the strength and ductility of products. Molybdenum (Mo) also has the effect of preventing a decrease in toughness caused by grain boundary segregation of impurity elements such as phosphorus (P). For this effect, 0.10% or more of molybdenum (Mo) can be added. However, since molybdenum (Mo) is an expensive element and excessive addition may significantly increase manufacturing costs, the upper limit of the molybdenum (Mo) content is limited to 0.12%.
[0029] Copper (Cu): 0.01-0.60% Copper (Cu) is an advantageous element in the present invention, since it not only can greatly improve the strength of the matrix phase by solid solution strengthening in ferrite, but also has the effect of suppressing corrosion in a wet hydrogen sulfide atmosphere. For this effect, 0.01% or more of copper (Cu) can be contained. A more preferable copper (Cu) content is 0.03% or more. However, if the copper (Cu) content is excessive, there is a high possibility that star cracks will be induced on the surface of the steel sheet, and furthermore, since copper (Cu) is an expensive element, there arises a problem that the manufacturing cost increases significantly. Therefore, in the present invention, the upper limit of the copper (Cu) content is limited to 0.60%. A more preferable upper limit of the copper (Cu) content is 0.35%.
[0030] Nickel (Ni): 0.05-1.00% Nickel (Ni) is an element that effectively contributes to improving strength by increasing stacking faults at low temperatures, facilitating cross slip of dislocations, improving impact toughness, and improving hardening ability. To achieve this effect, 0.05% or more of nickel (Ni) can be added. A preferred nickel (Ni) content is 0.10% or more. On the other hand, if nickel (Ni) is added in excess, the high cost may increase the manufacturing cost, so the upper limit of the nickel (Ni) content can be limited to 1.00%. A preferred upper limit of the nickel (Ni) content is 0.80%.
[0031] Calcium (Ca): 0.0005-0.0040% Adding calcium (Ca) after deoxidation with aluminum (Al) has the effect of suppressing the generation of MnS by combining with sulfur (S) that forms MnS inclusions, and suppressing the generation of cracks due to hydrogen-induced cracking by forming spherical CaS. In order to sufficiently form the sulfur (S) contained as an impurity into CaS, it is preferable to add 0.0005% or more of calcium (Ca). However, if the amount added is excessive, the calcium (Ca) remaining after forming CaS combines with oxygen (O) to generate coarse oxidized inclusions, which are stretched and broken during rolling and may be a factor in reducing the lamellar tear resistance. Therefore, it is better to limit the upper limit of the calcium (Ca) content to 0.0040%.
[0032] Equation 1 Ceq according to the following relational formula 1 is required to be in the range of 0.35 to 0.55. If Ceq according to the above relational formula 1 is less than 0.35, the pearlite fraction decreases, making it impossible to ensure the tensile strength value of 500 to 700 MPa required in the present invention, and if it exceeds 0.55, the pearlite fraction exceeds 30%, making it difficult to ensure the low-temperature impact energy value at -50°C. Therefore, Ceq in the present invention is preferably in the range of 0.35 to 0.55. [Relationship 1] Ceq=[C]+[Mn] / 6+([Cr]+[Mo]+[V]) / 5+([Ni]+[Cu]) / 15 In the above relational formula 1, [C], [Mn], [Cr], [Mo], [V], [Ni] and [Cu] respectively represent the contents (weight%) of C, Mn, Cr, Mo, V, Ni and Cu contained in the steel, and 0 is substituted when these elements are not intentionally added.
[0033] The extra-thick flange steel material and its product, which are excellent in strength and low-temperature impact toughness, according to the present invention, may contain the remaining Fe and other inevitable impurities in addition to the above-mentioned components. In normal manufacturing processes, unintended impurities may be inevitably mixed in from raw materials or the surrounding environment, and therefore, it is not possible to completely exclude them. Since these impurities are known to anyone with ordinary knowledge in this technical field, the entire contents of them are not specifically mentioned in this specification. Furthermore, the addition of further effective components in addition to the above-mentioned components is not completely excluded.
[0034] On the other hand, the extra heavy steel material of the present invention preferably has a fine structure in which the average crystal grain size of ferrite present in the center of the steel material is 25 μm or less, and which contains 5 to 30 area % pearlite and the remainder ferrite. If the average grain size of ferrite in the center of the steel exceeds 25μm, the crack path length during impact fracture becomes shorter, the Ductile Brittle Transition Temperature (DBTT) increases, and low-temperature impact toughness deteriorates. Therefore, it is appropriate that the average grain size of ferrite is 25μm or less. Furthermore, if the pearlite fraction in the microstructure of the steel is less than 5 area %, it is not appropriate to ensure a tensile strength value of 500 MPa or more, and if it exceeds 30 area %, the increase in hard structure may cause a deterioration in the low-temperature impact toughness value at -50°C.
[0035] In addition, the porosity of the center of the steel material, which is the region from the surface of the steel material to the thickness direction of 3 / 8t to 5 / 8t, is 0.05 mm 3 / g or less. In addition, the steel material of the present invention has deformation-induced NbC precipitates of 5 to 50 nm in size in the matrix structure. 2If the number of the deformation-induced NbC precipitates of 5 to 50 nm is less than 10, the precipitation strengthening effect is weakened, and if the number of the coarse precipitates of 100 nm or more is more than 5, the pinning effect and the precipitation strengthening effect are similarly lost, so that it is not easy to ensure the tensile strength of 500 to 700 MPa required in the present invention.
[0036] The extra heavy steel material of the present invention may have a thickness of 200 to 500 mm. Moreover, the extra heavy-gauge steel material of the present invention preferably has a tensile strength of 500 to 700 MPa, a yield strength of 350 MPa or more, and an absorbed energy value in a -60°C Charpy impact test of 50 J or more. The maximum surface crack depth of the steel material is preferably 0.1 mm or less (including 0).
[0037] Next, a method for producing an extra-thick steel material for flanges having excellent strength and low-temperature impact toughness, which is another aspect of the present invention, will be described in detail. The method for manufacturing an extra-thick steel material of the present invention includes the steps of preparing a slab having the above-mentioned compositional components, heating the slab to a temperature range of 1100 to 1300°C, performing a first upset of the heated slab with a forging ratio of 1.3 to 2.4, and then performing bloom forging at a forging ratio of 1.5 to 2.0, reheating the bloom forged material to a temperature range of 1100 to 1300°C, performing a second upset of the reheated bloom base material with a forging ratio of 1.3 to 2.3, and then performing round forging at a forging ratio of 1.65 to 2.25, and performing the round forging. The method includes a step of tertiary upsetting the forged material at a temperature equal to or lower than the recrystallization temperature defined by Relation 2 with a forging ratio of 2.0 to 2.8 so that the cumulative reduction is 10% or more; a step of reheating the tertiary upset material to a temperature range of 1100 to 1300°C after drilling holes, and then ring forging it with a forging ratio of 1.0 to 1.6; and a step of heating the ring forged material to a temperature range of 820 to 930°C as a temperature measurement standard for the center part, holding it for 5 to 600 minutes, and then normalizing it to room temperature.
[0038] Slab heating In the present invention, first, a slab having the above compositional components is prepared, and then heated to a temperature range of 1100 to 1300°C. The slab needs to be heated at a temperature above a certain range in order to redissolve titanium (Ti) and niobium (Nb) complex carbonitrides or TiNb (C, N) coarse crystals formed during casting. It is also preferable to heat the slab to a temperature above the recrystallization temperature before the first upset forging and hold it there to homogenize the structure, ensure a sufficiently high forging end temperature, and minimize surface cracks that may occur during the forging process. Therefore, the slab heating of the present invention is preferably performed at a temperature range of 1100°C or higher.
[0039] On the other hand, if the slab heating temperature is too high, high-temperature oxide scale may be excessively generated, and the manufacturing cost may increase excessively due to high-temperature heating and holding. Therefore, the primary heating of the slab in the present invention is preferably performed in the range of 1300°C or less. Meanwhile, in the present invention, the thickness of the slab can be 500 mm or more, and the preferred thickness is 700 mm or more.
[0040] Primary upset and bloom forging Next, in the present invention, the heated slab is subjected to a primary upset at a forging ratio of 1.3 to 2.4, and then to bloom forging at a forging ratio of 1.5 to 2.0. Upsetting is a method of performing strong plastic deformation perpendicular to the longitudinal axis, and the forging ratio in the first upsetting is preferably 1.3 to 2.4, and more preferably 1.5 to 2.0. Here, the forging ratio refers to the ratio of the cross-sectional area changed by forging. In such a first upsetting, if the size of the forged surface to be punched is initially 700 mm x 1800 mm, it can be (1000 to 1200 mm) x (1800 to 2000 mm).
[0041] If the forging ratio during the first upset is less than 1.3, it is difficult to sufficiently compress the porosity remaining in the center of the slab. Therefore, the porosity required in the final product of the present invention is set at an appropriate level of 0.05 mm 3 / g or less, it is difficult to ensure low-temperature impact toughness in the center. On the other hand, if the forging ratio in the first upset exceeds 2.4, buckling occurs during the forging process, making it difficult to achieve the surface quality and appropriate shape control required for flange products. Therefore, the forging ratio in the first upset is preferably 1.3 to 2.4. In the present invention, the primarily upset material is subjected to bloom forging at a forging ratio of 1.5 to 2.0.
[0042] Bloom forging is a method of processing a first upset material into a bloom shape by further pressing the material, and the area is expanded while processing both the upper and lower surfaces in a certain direction of width or length. In the case of bloom forging, if the size of the forged surface at the time of forging completion is initially (1000-1200mm) x (1800-2000mm), it can be (1450-1850mm) x (2100-2500mm). In the case of bloom forging, the forging ratio is preferably 1.5-2.0. If the forging ratio is less than 1.5, it is difficult to ensure the appropriate void quality required in the present invention, as in upset forging, and if it exceeds 2.0, surface cracks may occur. The forging direction can be either the length direction or the width direction, but in the case of the length direction, the cast structure is more dense, so the elongation rate of the surface layer structure is high and the workability is excellent. Therefore, the bloom forging in the length direction is more appropriate from the viewpoint of surface cracks than that in the width direction.
[0043] reheating In the present invention, the bloom forged material is reheated to a temperature range of 1100 to 1300°C. When the bloom forging is completed, the bloom surface temperature is 950°C or less, and if processing is continued, surface cracks or material breakage may occur. Therefore, after bloom forging, it is recommended to heat the material again to a temperature range of 1100 to 1300°C. As described above, it is preferable to heat the material to 1100°C or more for reasons such as re-dissolving the crystallized material, homogenizing the structure, and preventing surface cracks, and it is preferable to control the temperature to 1300°C or less due to problems such as excessive scaling and coarsening of crystal grains.
[0044] Secondary Upset - Round Forging Next, in the present invention, the reheated bloom material is subjected to secondary upsetting with a forging ratio of 1.3 to 2.3, and then round forging with a forging ratio of 1.65 to 2.25. That is, the bloom that has been heated is subjected to a secondary upsetting at a forging ratio of 1.3 to 2.3, and then round forging is performed at a forging ratio of 1.65 to 2.25 to process the bloom into a circular flange edge. When the secondary upsetting and round forging are completed, the product size can be (1450 to 1850Φ) x (1300 to 1700 mm). If the forging ratio during the secondary upsetting and round forging is less than the level required by the present invention, the porosity of the center of the final product is reduced to 0.05 mm 3 / g or less, and it is not easy to ensure low-temperature impact toughness at the center of the steel material. On the other hand, if the forging ratio exceeds the standard of the present invention, problems such as buckling, surface cracks, and shape defects occur, making it impossible to process into the desired flange product shape.
[0045] Tertiary upset (formation of deformation-induced precipitates) Next, in the present invention, the round forged material is tertiary upset at a temperature equal to or lower than the recrystallization temperature defined by the following Relation 2 with a forging ratio of 2.0 to 2.8 so that the cumulative reduction amount is 10% or more. The cylindrical material is processed to an appropriate flange thickness by a tertiary upsetting before piercing. When the tertiary upsetting is completed, the product size should be (2300~2800Φ) x (400~800mm). The forging ratio of the tertiary upset may be 2.0 to 2.8. If the forging ratio is insufficient or excessive, problems such as the above-mentioned inability to control residual voids and surface cracks / shape control may occur.
[0046] In this tertiary upsetting process, the important thing is the cumulative reduction at a temperature below the recrystallization temperature (Rst) of the steel material, and forging and rolling are performed so that the cumulative reduction is 10% or more. At this time, the recrystallization temperature can be calculated by the following Relation 2. [Equation 2] T nr (℃)=887+464×[C]+890×[Ti]+363×[Al]-357×[Si]+(6445×[Nb]-644×[Nb] 1 / 2 )+(732×[V]-230×[V] 1 / 2 ) In the above Relational Formula 2, [C], [Ti], [Al], [Si], [Nb], and [V] respectively represent the contents (weight%) of C, Ti, Al, Si, Nb, and V contained in the steel material, and 0 is substituted when these components are not intentionally added.
[0047] If the cumulative reduction is less than 10% at a temperature below the recrystallization temperature, the formation of deformation-induced ultrafine NbC or NbCN precipitates of 5 to 50 nm is not easy, and the precipitates are 1 μm 2There is a possibility that the number of precipitates per unit area is less than 10, or the number of coarse precipitates with a size of 100 nm or more exceeds 5. If the amount of fine precipitates decreases or the size increases, the precipitation strengthening effect is slight, and the pinning effect decreases during the subsequent normalizing temperature rise, making it difficult to control the average grain size of ferrite in the center of the product to 25 μm or less. Therefore, it is preferable to control the cumulative reduction at a temperature below the recrystallization temperature to 10% or more, more preferably 15% or more, and most preferably 20% or more.
[0048] Hole drilling and ring forging Next, in the present invention, the tertiary upset material is subjected to hole machining, reheated to a temperature range of 1100 to 1300° C., and then ring forging is performed with a forging ratio of 1.0 to 1.6. After the above-mentioned tertiary upsetting is completed, a hole can be drilled in the center of the material using a 500 to 1000Φ punch. The material with the holes machined is reheated again to the temperature range of 1100 to 1300°C, and then processed into the final flange ring shape. The maximum thickness of the flange made of the steel material can be 200 to 500 mm, the inner diameter is 4000 to 7000 mm, and the outer diameter is 5000 to 8000 mm. Ring forging is a process in which the final shape and dimensional control are more important than gap pressing, so severe plastic processing is not applied. Therefore, the forging ratio can be 1.0 to 1.6, and more preferably 1.2 to 1.4. Meanwhile, in the present invention, the deformation rate in all the forging processes presented above can be 1 / s to 4 / s. At a deformation rate of less than 1 / s, the temperature of the finish forging is lowered, and there is a possibility that surface cracks may occur. In contrast, when a high deformation rate of more than 4 / s is applied in the unrecrystallized region, there is a possibility that surface cracks may be induced due to a decrease in elongation caused by excessive local work hardening.
[0049] Normalizing heat treatment Finally, in the present invention, the ring-forged material is subjected to a normalizing heat treatment in which the material is heated to a temperature range of 820 to 930°C as a temperature measurement standard at the center, held for 5 to 600 minutes, and then air-cooled to room temperature. The flange product after the above forging is heated to a temperature range of 820 to 930°C as a temperature measurement standard at the center of the product (t / 2), and held for 5 to 600 minutes, and then normalized by air cooling to room temperature. If the heating temperature during the normalizing heat treatment is less than 820°C or the holding time is less than 5 minutes, the re-dissolution of carbides generated during cooling after forging and impurity elements segregated at grain boundaries may not occur smoothly, and the low-temperature toughness of the steel material after the heat treatment may be significantly reduced. On the other hand, if the heating temperature during the normalizing heat treatment exceeds 930°C or the holding time exceeds 600 minutes, the grain size of the ferrite matrix phase of the ferrite-pearlite composite structure may exceed 30 μm required in the present invention, or the precipitate phases such as Nb(C,N) and V(C,N) may become coarse, resulting in deterioration of strength and low-temperature impact toughness. EXAMPLES
[0050] The present invention will be described in detail below with reference to examples. However, it should be noted that the following examples are intended to illustrate and explain the present invention in more detail, and are not intended to limit the scope of the present invention. (Example)
[0051] [Table 1] *In Table 1, the content units of the component elements are in weight percent, but the units of P, S, and Ca are in ppm, and the remaining components are Fe and inevitable impurities.
[0052] A 700 mm thick slab was manufactured using the alloy composition shown in Table 1. Using this slab, a 320 mm thick flange was finally manufactured through the slab preparation, forging process (reheating and first upset, bloom forging, reheating, second upset-round forging, third upset, reheating and ring forging) and normalizing heat treatment, which are process conditions shown in Table 2 below. At this time, the reheating temperature for the second upset after the bloom forging was 1230°C ± 10°C, and the forging ratio of the round forging after the second upset was 2.0, which was also applied. All process conditions other than those shown in Table 2 below were applied within the scope of the present invention. Thereafter, the physical properties of each of the test pieces produced above were measured and are shown in Table 3 below. Here, the grain size of ferrite and the phase fraction of ferrite were measured by taking a test piece from the central part of the structure test piece after normalizing heat treatment and using an automatic image analyzer. Meanwhile, in this example, the microstructure of the products in all of the invention examples and comparative examples is a mixed structure of ferrite and pearlite.
[0053] The yield / tensile strength was evaluated by a room temperature tensile test according to ASTM A370, with a 0.2% offset applied to the yield strength. The impact toughness of each test piece was calculated by using the average absorbed energy measured three times at the same temperature through a Charpy V-Notch test. The number of deformation-induced NbC precipitates of 5 to 50 nm observed in the cross section of the steel material was measured using a TEM. NbC precipitates were confirmed by the NbC diffraction pattern and EDX mapping, and the precipitates were measured at 1 μm. 2 The number of NbC precipitates located at the positions were counted. The porosity of the product center is the density (g / mm 3 ) and reciprocal (mm 3 It was measured by taking the mass (g). In addition, after visually observing the surface of each test piece, the surface was ground at the point where a surface crack had formed, and the length ground until the crack disappeared was measured as the surface crack length.
[0054] [Table 2]
[0055] [Table 3] *In Table 3, a* is the 1μm diameter of deformation-induced NbC precipitates of 5 to 50 nm observed in the cross section of the steel material. 2 b* indicates the number of coarse precipitates of 100 nm or more.
[0056] As can be seen from Tables 1 to 3 above, in the case of Examples 1 to 5, which satisfy the alloy composition and manufacturing conditions proposed by the present invention, not only do they have excellent strength and excellent low-temperature impact toughness at -50°C, but they also have good surface quality in the flange product state. In contrast, Comparative Examples 1 to 8 satisfy the alloy composition proposed by the present invention but do not satisfy the manufacturing conditions, and therefore do not satisfy the characteristics proposed by the present invention, such as the porosity of the center and the ferrite grain size in the flange product state, and therefore have low levels of strength and low-temperature impact toughness. Even if the material quality is good, if the forging ratio conditions at each forging stage are not satisfied, poor surface quality characteristics in the product state can be confirmed by the occurrence of surface cracks or through cracks. On the other hand, Comparative Examples 9 to 13 satisfy the manufacturing conditions proposed by the present invention, but do not satisfy the alloy composition, and are found to have low quality levels, such as excessive strength (insufficient impact toughness) or insufficient strength.
[0057] As described above, the detailed description of the present invention has been given of the preferred embodiment of the present invention, but it goes without saying that a person having ordinary skill in the art to which the present invention pertains can make various modifications without departing from the scope of the present invention. Therefore, the scope of the present invention should not be limited to the described embodiment, but should be determined by the claims below as well as equivalents thereto.
Claims
1. In weight percent, C: 0.05-0.2%, Si: 0.05-0.5%, Mn: 1.0-2.0%, Al: 0.005-0.1%, P: 0.01% or less, S: 0.015% or less, Nb: 0.001-0.07%, V: 0.001-0.3%, Ti: 0.001-0.03%, Cr: 0.01-0.3%, Mo: 0.01-0.12%, Cu: 0.01-0.6%, Ni: 0.05-1.0%, Ca: 0.0005-0.004%, with the remainder being Fe and other unavoidable impurities, and Ceq according to the following relational formula 1 satisfies the range of 0.35-0.55, The average crystal grain size of ferrite present at the center of the steel material is 25 μm or less, and the steel material has a fine structure containing 5 to 30 area % of pearlite and the remainder of ferrite, The porosity of the center of the steel material, which is the region from the surface of the steel material to the thickness direction of 3 / 8t to 5 / 8t, is 0.05 mm 3 / g or less, and Deformation-induced NbC precipitates of 5 to 50 nm observed in the cross section of the steel material are 1 μm 2 10 or more precipitates per square centimeter, and 5 or less coarse precipitates of 100 nm or more. [Relationship 1] Ceq=[C]+[Mn] / 6+([Cr]+[Mo]+[V]) / 5+([Ni]+[Cu]) / 15 In the above Relational Formula 1, [C], [Mn], [Cr], [Mo], [V], [Ni] and [Cu] respectively mean the contents (weight %) of C, Mn, Cr, Mo, V, Ni and Cu contained in the steel material, and 0 is substituted when these components are not intentionally added.
2. 2. The extremely thick steel material for flanges according to claim 1, characterized in that the steel material has a thickness of 200 to 500 mm.
3. The extra-thick steel material for flanges according to claim 1, characterized in that the steel material has a tensile strength of 500 to 700 MPa, a yield strength of 350 MPa or more, and an absorbed energy value of 50 J or more in a -50°C Charpy impact test.
4. 2. The extremely thick steel material for flanges according to claim 1, characterized in that the maximum surface crack depth of the steel material is 0.1 mm or less (including 0).
5. A step of preparing a slab having, in weight percent, C: 0.05-0.2%, Si: 0.05-0.5%, Mn: 1.0-2.0%, Al: 0.005-0.1%, P: 0.01% or less, S: 0.015% or less, Nb: 0.001-0.07%, V: 0.001-0.3%, Ti: 0.001-0.03%, Cr: 0.01-0.3%, Mo: 0.01-0.12%, Cu: 0.01-0.6%, Ni: 0.05-1.0%, Ca: 0.0005-0.004%, and the remainder being Fe and other inevitable impurities, and having a Ceq of 0.35-0.55 according to the following relational formula 1, heating the slab to a temperature range of 1100-1300 ° C.; performing a first upsetting of the heated slab at a forging ratio of 1.3 to 2.4, and then bloom forging at a forging ratio of 1.5 to 2.0; reheating the bloom forged material to a temperature range of 1100 to 1300°C; Secondarily upsetting the reheated bloom material at a forging ratio of 1.3 to 2.3, and then round forging at a forging ratio of 1.65 to 2.25; The round forged material is subjected to a third upsetting at a temperature equal to or lower than the recrystallization temperature defined by the following Relation 2, with a forging ratio of 2.0 to 2.8 so that the cumulative reduction is 10% or more; After the tertiary upset material is drilled, it is reheated to a temperature range of 1100 to 1300 ° C., and then ring forged with a forging ratio of 1.0 to 1.6; and heating the ring-forged material to a temperature range of 820 to 930°C based on the temperature measurement standard at the center of the material, holding the temperature for 5 to 600 minutes, and then air-cooling the material to room temperature (normalizing heat treatment). [Relationship 1] Ceq=[C]+[Mn] / 6+([Cr]+[Mo]+[V]) / 5+([Ni]+[Cu]) / 15 In the above Relational Formula 1, [C], [Mn], [Cr], [Mo], [V], [Ni] and [Cu] respectively mean the contents (weight %) of C, Mn, Cr, Mo, V, Ni and Cu contained in the steel material, and 0 is substituted when these components are not intentionally added. [Relationship 2] T nr (℃)=887+464×4C5+890×4Ti+363×4A5-357×4Si5++6445×4'5-6445- 1/2 )+(732×〔V〕-230×〔V〕 1/2 ) In the above Relational Formula 2, [C], [Ti], [Al], [Si], [Nb], and [V] respectively mean the contents (wt%) of C, Ti, Al, Si, Nb, and V contained in the steel material, and 0 is substituted when these components are not intentionally added.
6. 6. The method of claim 5, wherein the slab is manufactured using one of a continuous casting process, a semi-continuous casting process, and an ingot casting process.
7. The method for manufacturing an extremely thick steel material for flanges according to claim 5, characterized in that the size of the forging surface punched out during the first upsetting is (1000-1200 mm) x (1800-2000 mm) when the size is initially 700 mm x 1800 mm.
8. In the case of the bloom forging, the size of the forged surface at the time of forging completion is initially (1000-1200 mm) x (1800-2000 mm), and then is (1450-1850 mm) x (2100-2500 mm). The method for manufacturing an extremely thick steel material for flanges according to claim 5, characterized in that
9. The manufacturing method of the extra thick steel material for flanges according to claim 5, characterized in that when the secondary upsetting and round forging are completed, the size of the product is (1450 to 1850Φ) x (1300 to 1700 mm).
10. The method for manufacturing an extremely thick steel material for flanges according to claim 5, characterized in that when the tertiary upsetting is completed, the size of the product is (2300 to 2800Φ) x (400 to 800 mm).
11. The method for manufacturing an extremely thick steel material for flanges according to claim 5, characterized in that the maximum thickness of the flange made of the steel material can be 200 to 500 mm, the inner diameter is 4000 to 7000 mm, and the outer diameter is 5000 to 8000 mm.
Citation Information
Patent Citations
A thick steel plate for wind turbine flanges and its manufacturing method
CN109338219B
Rolling h-shaped steel and manufacturing method therefor, and flange weld joint of rolling h-shaped steel
JP2016117945A
Thick high-toughness high-strength steel sheet and its manufacturing method
JP5928654B2
Ultra thick steel sheet for pressure vessel having excellent central properties and hydrogen induced cracking resistance, and method for manufacturing the same
KR101253890B1
Mask
KR1020220128147A
Cited By
Ultra-thick steel material for flange with excellent strength and low-temperature impact toughness and method for manufacturing the same
JP2025521378A